Fitness for Service Evaluations and Non-Linear Analysis 2002
DOI: 10.1115/pvp2002-1322
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis of Anchored Tanks Subject to Equivalent Seismic Loading

Abstract: The finite element method is applied to the problem of the nonlinear behavior of anchored cylindrical liquid-storage tanks subject to horizontal seismic loading. The tank alone is modelled with assumptions of fixed conditions at the base and free conditions at the top. Geometric nonlinearity is considered and the material behavior is taken as elastic-perfectly plastic. The loading consists of a constant hydrostatic pressure to which is added an equivalent static pressure representing hydrodynamic effects arisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Computational dynamic buckling analyses considering geometric and material nonlinearity have been performed for tank structures subjected to earthquakes. Using experimental or computational methods, Liu and Lam [1983], Natsiavas and Babcock [1987], Nagashima et al [1987], Redekop et al [2002], and Morita et al [2003] reported the occurrence of buckling at the top of tanks induced by horizontal base excitations. In their experimental dynamic buckling studies, Natsiavas and Babcock [1987] considered a tall tank with an open top undergoing a horizontal harmonic base acceleration.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Computational dynamic buckling analyses considering geometric and material nonlinearity have been performed for tank structures subjected to earthquakes. Using experimental or computational methods, Liu and Lam [1983], Natsiavas and Babcock [1987], Nagashima et al [1987], Redekop et al [2002], and Morita et al [2003] reported the occurrence of buckling at the top of tanks induced by horizontal base excitations. In their experimental dynamic buckling studies, Natsiavas and Babcock [1987] considered a tall tank with an open top undergoing a horizontal harmonic base acceleration.…”
Section: Introductionmentioning
confidence: 98%
“…However, dynamic buckling analyses are very expensive and thus the buckling evaluation must frequently rely on static analyses. Fischer and Rammerstorfer [1982] and Redekop et al [2002] used static buckling analyses for the seismic evaluation of steel tanks, and presented the results in terms of the critical spectral acceleration that induces buckling. A simplified nonlinear analysis for the seismic design of liquid storage tanks was proposed by Malhotra [2000] based on the nonlinear static procedure for buildings [ATC-40, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…[11] and Morita et al [12]. The dynamic buckling studies by Natsiavas and Babcock [9] considered an open-top tank under horizontal harmonic base acceleration for a tall tank with a height to diameter ratio H /D = 2.1.…”
Section: Introductionmentioning
confidence: 98%